Curing composition for absorbing carbon dioxide and / or nitrogen-based malodorous substance and application thereof
A curable composition with magnesium oxide, magnesium carbonate, and gypsum hemihydrate absorbs carbon dioxide and nitrogen-based malodorous substances, addressing emission and air quality issues in building materials, thereby reducing environmental impact.
Patent Information
- Application Number
- JP2023096217
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing building materials used for finishing floors and walls do not effectively reduce carbon dioxide emissions or absorb nitrogen-based malodorous substances, despite the demand for such countermeasures.
A curable composition containing magnesium oxide, magnesium carbonate, gypsum hemihydrate, and a silicate compound, with specific ratios and properties, which absorbs carbon dioxide and nitrogen-based malodorous substances during curing, forming a cured product suitable for flooring and wall applications.
The composition significantly reduces carbon dioxide emissions and improves indoor air quality by absorbing nitrogen-based malodorous substances like ammonia and trimethylamine, enhancing the environmental impact of building materials.
Smart Images

Figure 2024177852000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a curable composition for absorbing carbon dioxide and / or nitrogen-based malodorous substances, which is used on floors and walls, and uses thereof. [Background technology]
[0002] Cement is used as a building material when constructing office buildings and apartment buildings, but it is known that cement emits large amounts of carbon dioxide when burned during its production.
[0003] In recent years, there has been a demand to reduce carbon dioxide emissions not only when constructing buildings with environmental considerations in mind, but also when producing the cement used in construction.
[0004] For this reason, technologies have been developed to reduce carbon dioxide emissions by improving the mix of concrete and mortar-based materials that use cement as a hardening binder. For example, Patent Document 1 discloses a hydraulic composition that is characterized by containing a pozzolanic component and an alkaline component, and describes that the production of this hydraulic composition involves a carbonation treatment and does not involve a firing treatment, so that carbon dioxide emissions can be reduced or carbon dioxide absorption can be increased.
[0005] Furthermore, in recent years, in order to curb the total amount of carbon dioxide emissions during the construction of a building, there has been a demand to reduce carbon dioxide emissions not only from cement but also from building materials used for finishing floors and walls.
[0006] As a technology for reducing carbon dioxide emissions from building materials used in such finishing, for example, Patent Document 2 discloses an earth-based block that is a mixture of soil aggregate, a solidifying agent containing magnesium oxide and magnesium chloride, and phosphoric acid, which is molded into a paving block and exhibits the strength required for a paving material. It is described that because the blocks do not use cement in their production, large amounts of carbon dioxide emissions can be avoided. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2022-153131 A [Patent Document 2] JP 2023-15438 A [Patent Document 3] Patent No. 7130291 Summary of the Invention [Problem to be solved by the invention]
[0008] However, technology to reduce carbon dioxide emissions from building materials used in finishing, or technology to absorb carbon dioxide, is still in its infancy, and no effective examples of countermeasures have been identified. [Means for solving the problem]
[0009] Therefore, an object of the present invention is to provide a technology for reducing or absorbing carbon dioxide emissions from building materials used in finishing.
[0010] Meanwhile, the present inventors have reported a hydraulic composition that can be used as a building material for finishing floors and walls (Patent Document 3). As a result of further intensive research into this hydraulic composition, they discovered that the hydraulic composition absorbs carbon dioxide in the process of becoming a hardened material, and also absorbs nitrogen-based malodorous substances such as ammonia and trimethylamine at the same time, and thus completed the present invention.
[0011] The present inventors also found that the cured product obtained as described above also absorbs carbon dioxide, and at the same time, absorbs nitrogen-based malodorous substances such as ammonia and trimethylamine, and thus completed the present invention.
[0012] That is, the present invention is as follows. (1) A hardenable composition containing magnesium oxide, magnesium carbonate, hemihydrate gypsum, and a silicate compound, Contains 30 to 60 mass% magnesium oxide, Magnesium oxide with an average BET specific surface area of 5 to 25 m 2 / g, The mass ratio of magnesium oxide to magnesium carbonate is 3 to 10:1; The amount of hemihydrate gypsum is 6 to 25% by mass based on the mass of magnesium oxide, Does not contain magnesium chloride A curable composition for absorbing carbon dioxide and / or nitrogen-based malodorous substances, comprising: (2) A hardened body for absorbing carbon dioxide and / or nitrogen-based malodorous substances, obtained by hardening a mixture of the above-mentioned hardenable composition for absorbing carbon dioxide and / or nitrogen-based malodorous substances and water. (3) A molded body for absorbing carbon dioxide and / or nitrogen-based malodorous substances, which is obtained by pouring a mixture of the above-mentioned hardening composition for absorbing carbon dioxide and / or nitrogen-based malodorous substances and water into a mold and hardening the mixture. (4) A method for absorbing carbon dioxide and / or nitrogen-based malodorous substances, comprising applying a mixture of the above-mentioned carbon dioxide and / or nitrogen-based malodorous substance absorbing hardening composition and water to a floor surface, and then hardening the mixture. (5) A method for absorbing carbon dioxide and / or nitrogen-based malodorous substances, comprising applying a mixture of the above-mentioned carbon dioxide and / or nitrogen-based malodorous substance absorbing hardening composition and water to a wall surface, and then hardening the mixture. (6) A method for absorbing carbon dioxide and / or nitrogen-based malodorous substances, comprising pouring a mixture of the above-mentioned hardening composition for absorbing carbon dioxide and / or nitrogen-based malodorous substances and water into a formwork and then hardening the mixture. (7) A method for absorbing carbon dioxide and / or nitrogen-based malodorous substances, comprising attaching the above-mentioned carbon dioxide and / or nitrogen-based malodorous substance absorbing molded article to a floor surface. (8) A method for absorbing carbon dioxide and / or nitrogen-based malodorous substances, comprising attaching the above-mentioned carbon dioxide and / or nitrogen-based malodorous substance absorbing molded article to a wall surface. Effect of the Invention
[0013] The curable composition for absorbing carbon dioxide and / or nitrogen-based malodorous substances of the present invention absorbs carbon dioxide and / or nitrogen-based malodorous substances during curing and even when the cured or molded body is used as a finishing building material.
[0014] Therefore, the present invention can be useful in reducing the total amount of carbon dioxide emissions when constructing a building, and also in improving the indoor environment by reducing nitrogen-based odorous substances such as ammonia and trimethylamine inside the building. [Brief description of the drawings]
[0015] [Figure 1] FIG. 13 is a graph showing the results of the carbon dioxide absorption test in Example 6. [Diagram 2] FIG. 13 is a graph showing the results of a carbon dioxide absorption test in Example 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] In this specification, the hardenable composition refers to a composition that is hardened by curing a mixture obtained by kneading the composition with water (this refers to the same as the hydraulic composition in Patent Document 3).
[0017] In the present specification, the nitrogen-based malodorous substances are not particularly limited, but examples thereof include ammonia, methylamine, dimethylamine, trimethylamine, etc., and preferably refer to ammonia and trimethylamine.
[0018] The hardenable composition for absorbing carbon dioxide and / or nitrogen-based malodorous substances of the present invention (hereinafter simply referred to as "the composition of the present invention") is a hardenable composition containing magnesium oxide, magnesium carbonate, hemihydrate gypsum, and a silicate compound, and contains 30 to 60 mass % of magnesium oxide and has an average BET specific surface area of 5 to 25 m. 2 / g, the mass ratio of magnesium oxide to magnesium carbonate is 3 to 10:1, the amount of gypsum hemihydrate is 6 to 25 mass% relative to the mass of magnesium oxide, and no magnesium chloride is contained.
[0019] The magnesium oxide has an average BET specific surface area of 5 to 25 m from the viewpoint of the pot life of the resulting curable composition and physical properties such as strength of the cured product. 2 / g is preferable, and 10 to 20m 2 / g is more preferable. When using magnesium oxide having the above average BET specific surface area, one having an average BET specific surface area in this range may be used alone, or a combination of a plurality of average BET specific surface areas in this range may be used. The average particle size of magnesium oxide is not particularly limited, but is, for example, 1.0 to 6.0 μm, preferably 3.0 to 4.5 μm. Such magnesium oxide may be obtained by actually measuring the BET specific surface area and average particle size of commercially available magnesium oxide, selecting magnesium oxide that meets the above conditions, and combining them appropriately. Specifically, such magnesium oxide can be obtained from Konoshima Chemical Co., Ltd., Ako Chemical Industry Co., Ltd., Tateho Chemical Industry Co., Ltd., Kyowa Chemical Industry Co., Ltd., etc.
[0020] The BET specific surface area of magnesium oxide is a value measured using a flow type automatic specific surface area measuring device (Flowsorb 2300 type: manufactured by Shimadzu Corporation) in accordance with JIS R1626 (Method for measuring specific surface area of fine ceramic powder by gas adsorption BET method). The average BET specific surface area of magnesium oxide refers to a value measured by the gas adsorption BET method after mixing two or more types of magnesium oxide with different BET specific surface areas. Furthermore, the average particle size of magnesium oxide is the average value of values measured by a Microtrac particle size distribution analyzer (model HRA type: manufactured by Nikkiso Co., Ltd.) after dispersing the sample for 3 minutes using an ultrasonic dispersing device (UD-201: manufactured by Nippon Seiki Seisakusho Co., Ltd.) after placing the sample in a dispersion medium (denatured alcohol).
[0021] The content of magnesium oxide in the composition of the present invention is 30 to 60 mass % (hereinafter simply referred to as "%"), and preferably 35 to 50%.
[0022] The magnesium carbonate is not particularly limited, but is preferably basic magnesium carbonate. Basic magnesium carbonate is generally represented by the following formula: <expression> mMgCO3 Mg(OH)2 nH2O (where m=3-5, n=3-7) The average BET specific surface area of basic magnesium carbonate is not particularly limited, but is, for example, 10 to 60 m 2 / g, preferably 20 to 50m 2 / g. The basic magnesium carbonate having the above average BET specific surface area may have an average BET specific surface area in this range, or may have a combination of a plurality of average BET specific surface areas in this range. The average particle size of the basic magnesium carbonate is not particularly limited, but is 0.5 to 100 μm, preferably 5 to 20 μm. The average BET specific surface area and average particle size of the basic magnesium carbonate can be measured in the same manner as for magnesium oxide.
[0023] The mass ratio of magnesium oxide to magnesium carbonate in the composition of the present invention is 3-10:1, preferably 5-9:1.
[0024] The above-mentioned hemihydrate gypsum is also called calcined gypsum and is expressed as CaSO4·1 / 2H2O. The alpha and beta types of hemihydrate gypsum are known, but either or both types may be used.
[0025] The content of hemihydrate gypsum in the composition of the present invention is 6 to 25% and preferably 8 to 20% by mass of magnesium oxide from the viewpoints of the pot life of the obtained hardenable composition and physical properties such as strength of the hardened product.
[0026] The silicate compound is not particularly limited, and examples thereof include wollastonite, kaolinite, metakaolin, zircon, talc, mica, and dry silica. Among these silicate compounds, a combination of wollastonite and one or more silicate compounds other than wollastonite is preferred, and a combination of wollastonite and one or more selected from the group consisting of metakaolin, zircon, and dry silica is more preferred. Wollastonite is a fine powder of wollastonite, a natural inorganic mineral, and is represented by CaSiO3. Wollastonite contains silicic acid components and has a needle-shaped crystal structure, so it is preferable to use it as an essential component because it can be expected to have a dimensional stability effect on the hardened structure. Kaolinite is a fine powder of natural kaolinite, and is represented by Al4Si4O 10 It is represented by (OH)8. Metakaolin, also known as semi-calcined kaolin, is represented by anhydrous aluminum silicate, Al2O3·2SiO2. This metakaolin is produced by heating and calcining kaolinite at 700-900℃. Zircon (zirconium silicate) is a silicate mineral of zirconium, represented by ZrSiO4. It is preferable to use zircon that has been pulverized to a particle size of 50μm or less, and is commercially available under the trade names of Zircon and Zircon Flower, for example. Talc is a mineral composed of magnesium hydroxide and silicate, also known as talc, and is expressed as Mg3Si4O 10 It is expressed as (OH)2. Mica, known in Japanese as 'Kika', is a silicate mineral made up of silicon, aluminum, magnesium, potassium, etc., and is characterized by its scaly crystal structure. Dry silica, also known as fumed silica, is expressed as SiO2. This dry silica has a small primary particle size of 50nm or less, and multiple particles are linked together like beads to form very bulky aggregates, so even a very small amount can be used to achieve the desired effect.
[0027] The content of the silicate compound in the composition of the present invention is not particularly limited, but is, for example, 0.1 to 30%, preferably 0.2 to 25%, based on the mass of magnesium oxide in terms of the pot life of the obtained curable composition and physical properties such as the strength of the cured product. In particular, when the silicate compound contains dry silica, the dry silica is bulky, and when the content is high, the viscosity of the material becomes too high, so the content of dry silica is preferably low, 3% or less, based on the mass of magnesium oxide. Wollastonite has a needle-like shape, but has little effect on the viscosity of the material, and can be blended up to about 30% based on the mass of magnesium oxide, which is effective in improving dimensional stability. In addition, when wollastonite and one or more silicate compounds other than wollastonite are used in combination as the silicate compound, the mass ratio of wollastonite to silicate compounds other than wollastonite is 1:0.01 to 1, preferably 1:0.01 to 0.8.
[0028] In addition to the above essential components, the composition of the present invention may further contain one or more compounding agents selected from the group consisting of fillers, pigments, water-reducing agents, antifoaming agents, wetting and dispersing agents, viscosity adjusters, anti-sagging agents, water-based resins, and aggregates. Basically, these compounding agents may be appropriately compounded in amounts suited to the intended use of the composition of the present invention.
[0029] The filler has a role of adjusting viscosity for workability, improving strength properties of the cured product, and acting as an extender, and examples thereof include calcium carbonate, silica powder, silica sand, baryte powder, etc. The content of the filler in the composition of the present invention is not particularly limited, but is, for example, 10% or more, preferably 20 to 70%, and more preferably 30 to 60%.
[0030] Examples of the pigment include inorganic pigments, organic pigments, and special pigments. Specific examples of inorganic pigments include natural mineral pigments such as red clay, ocher, green clay, malachite, chalk powder, and graphite, and synthetic inorganic pigments such as iron blue, zinc oxide, cobalt blue, emerald green, viridian, titanium white, and iron oxide. Specific examples of organic pigments include alkali blue, lysol red, carmine 6B, disazo yellow, phthalocyanine blue, quinacridone red, and isoindolinone yellow. Specific examples of special pigments include fluorescent pigments, metal powder pigments, pearl pigments, thermochromic pigments, and ceramic pigments. The content of the pigment in the curable composition of the present invention is not particularly limited, but is, for example, 0.1% or more, preferably 0.2 to 2.0%, and more preferably 0.4 to 1.5%.
[0031] Examples of the water reducing agent include AE agents, water reducing agents / AE water reducing agents, high performance water reducing agents, high performance AE water reducing agents, etc. The content of the water reducing agent in the composition of the present invention is not particularly limited, but is, for example, 0.05% or more, preferably 0.1 to 1.5%, and more preferably 0.2 to 1.0%.
[0032] The above-mentioned defoaming agent may be, for example, a mineral oil-based compound, a polyether-based compound, a silicone-based compound, etc. In addition, these defoaming agents may be in the form of powder. Furthermore, the content of the defoaming agent in the composition of the present invention is not particularly limited, but is, for example, 0.01% or more, preferably 0.05 to 2.0%, more preferably 0.1 to 1.5%.
[0033] Examples of the wetting and dispersing agent include anionic compounds, cationic compounds, nonionic compounds, and polymeric compounds. Specific examples of the wetting and dispersing agent include aliphatic polycarboxylic acid compounds, aminoamide compounds, phosphate compounds, nonionic compounds, acrylic polymers, and polyether phosphate compounds. The content of the wetting and dispersing agent in the composition of the present invention is not particularly limited, but is, for example, 0.01% or more, preferably 0.02 to 1.0%, and more preferably 0.03 to 0.5%.
[0034] Examples of the viscosity modifier include urethane-modified polyether compounds, acrylic polymers, amide compounds, polyether phosphate ester compounds, hydrogenated castor oil compounds, fumed silica compounds, bentonite compounds, layered silicate compounds, etc. The content of the viscosity modifier in the composition of the present invention is not particularly limited, but is, for example, 0.01% or more, preferably 0.02 to 1.0%, and more preferably 0.03 to 0.5%.
[0035] Examples of the sagging prevention agent include cellulose compounds, starch ester compounds, polyacrylamide compounds, synthetic polymer compounds, etc. The content of the sagging prevention agent in the composition of the present invention is not particularly limited, but is, for example, 0.01% or more, preferably 0.02 to 1.0%, and more preferably 0.03 to 0.5%.
[0036] Examples of the aqueous resin include re-emulsified powder resin and polymer dispersion. Examples of the re-emulsified powder resin include acrylic resin, vinyl acetate resin, and ethylene-vinyl acetate copolymer resin. Examples of the polymer dispersion include styrene-butadiene rubber latex, acrylic acid ester emulsion, and ethylene-vinyl acetate emulsion. Since the polymer dispersion is a dispersion of an aqueous resin in water, when blending, it may be contained together with water, which will be described later. Furthermore, the content of the aqueous resin in the composition of the present invention is not particularly limited, but is, for example, 0.5% or more, preferably 1.0 to 10.0%, and more preferably 2.0 to 6.0%.
[0037] Examples of aggregates include gravel, crushed stone, artificial aggregate, magnetite, barite, iron pieces, expanded slag, perlite, etc. The content of the aggregate in the composition of the present invention is not particularly limited, but is, for example, 5 parts by mass or more, preferably 10 to 100 parts by mass, and more preferably 20 to 80 parts by mass, per 100 parts by mass of the composition of the present invention.
[0038] It should be noted that the composition of the present invention may be formulated without containing magnesium chloride.
[0039] More preferred embodiments of the composition of the present invention include those containing the following components, and particularly preferred embodiments include those consisting of the following components. (Composition 1) Magnesium oxide 30 to 55 parts by mass Magnesium carbonate 3 to 15 parts by mass Gypsum hemihydrate 3~10 parts by mass Silicate compound 0.1 to 30 parts by mass Filler 20~50 parts by mass Compounding agents other than fillers: 0.5 to 5 parts by mass (Composition 2) Magnesium oxide 30 to 55 parts by mass Magnesium carbonate 3 to 15 parts by mass Gypsum hemihydrate 3~10 parts by mass Silicate compound 0.1 to 30 parts by mass Mass ratio of wollastonite to silicate compounds other than wollastonite =1:0.01~1 Filler 20~50 parts by mass Compounding agents other than fillers: 0.5 to 5 parts by mass
[0040] The composition of the present invention described above can be kneaded with water to form a kneaded product. The method for preparing the kneaded product is not particularly limited, but for example, a method for preparing a kneaded product by adding water to the composition of the present invention and kneading the composition is exemplified. The content of water in the kneaded product is not particularly limited as long as the curing reaction occurs sufficiently, but is an amount such that the mass ratio of the total mass of magnesium oxide, magnesium carbonate, hemihydrate gypsum, and silicate compound to water is 1:0.5 to 1.0, preferably 1:0.6 to 0.9.
[0041] The kneaded product can be applied to floor surfaces, wall surfaces, etc., and cured to form a cured product, or can be cured in a formwork to form a molded product. Curing can be carried out at room temperature (5 to 35°C). This kneaded product has an appropriate curing reaction time, for example, a pot life of about 15 to 30 minutes and a curing time of about 15 to 30 hours. The pot life is measured by the method described in the examples, and the curing time is an estimate of the time a person can stand on the applied kneaded product.
[0042] The composition of the present invention absorbs carbon dioxide and / or nitrogen-based malodorous substances during hardening. Here, absorbing carbon dioxide means that the composition of the present invention is kneaded with water to start a hardening reaction, and at the same time, carbon dioxide is taken into the hardened body, resulting in the phenomenon of absorbing carbon dioxide present in the surrounding environment. In addition, absorbing nitrogen-based malodorous substances means that in the process of the hardening of the composition of the present invention progressing and forming a hardened body, fine pores are formed in the hardened structure, and the pores are presumed to adsorb particles of nitrogen-based malodorous substances. In addition, the hardened product of the composition of the present invention reaches complete hardening after a considerable curing period, but in the process before complete hardening, the carbon dioxide absorption amount decreases compared to immediately after kneading, but the carbon dioxide absorption performance continues slowly. Furthermore, since the hardened product of the composition of the present invention has fine pores formed in its structure, the adsorption effect of particles of nitrogen-based malodorous substances can be confirmed.
[0043] To measure the amount of carbon dioxide and / or nitrogen-based malodorous substances absorbed, a gas collection bag is used, a measured sample is placed in it, the open part of the bag is sealed by heat sealing, and immediately, carbon dioxide and / or nitrogen-based malodorous substances with a predetermined concentration are injected into the bag from the injection valve. After that, the concentration of each substance in the collection bag is measured every time, and the amount of absorption can be measured.
[0044] In addition, the concentration of carbon dioxide can be measured using a concentration meter with a built-in carbon dioxide sensor, but since a gas collection bag is used, the method of measurement using a gas detection tube is simple and easy to operate.
[0045] On the other hand, the concentration of nitrogen-based malodorous substances can be measured by gas chromatography or absorptiometry, but they can also be easily measured by a gas detector tube, just like the concentration of carbon dioxide.
[0046] It is known that common Portland cements absorb carbon dioxide during the hardening process and long-term curing process when used as concrete or mortar. This causes carbonation in the concrete, lowering its alkalinity, a phenomenon known as neutralization of concrete. While the initial alkalinity of concrete is pH 12-13, depending on the environmental conditions and the quality of the materials, it can fall below pH 10 over time. In the case of reinforced concrete, neutralization can cause corrosion (rust) of the reinforcing bars, which is a major problem.
[0047] On the other hand, the pH of the kneaded product obtained by adding water to the composition of the present invention is about 10 to 11, but since it is not used for applications such as reinforced concrete, but is used as a so-called finishing material to be applied to floors, walls, etc., the above-mentioned problems do not occur. In addition, since it is used as a molded tile in a hardened state in advance, there is also no problem with pH.
[0048] In addition, by adding water to the composition of the present invention and curing the kneaded product obtained in the presence of carbon dioxide, the strength of the resulting cured product or molded body is improved. The concentration of carbon dioxide during curing is not particularly limited, but for example, when a product whose bending strength is 15.0 MPa after curing and curing in indoor air is cured in an environment with a carbon dioxide concentration of 20%, the bending strength becomes 18.7 MPa after the same curing period, and it was confirmed that the strength is improved by about 25%.
[0049] The thus obtained cured product or molded product of the present invention also absorbs carbon dioxide and / or nitrogen-based malodorous substances, like the composition of the present invention.
[0050] Furthermore, the hardened body or molded body of the present invention may be coated with a top coat, which is usually applied since it does not significantly affect the ability of the hardened body or molded body of the present invention to absorb carbon dioxide and / or nitrogen-based malodorous substances. The type of top coat is not particularly limited, but if the material has a high solid content that completely shields the surface of the hardened body or molded body of the present invention, the amount of absorption will decrease, so the solid content concentration of the top coat material is desirably 50% or less, and preferably 30% or less to suppress the decrease in absorption capacity. Furthermore, the amount of application is not particularly limited, but if an excessive amount is applied, the absorption capacity will decrease, so it is preferable to use the minimum amount of application necessary.
[0051] The hardened and molded products of the present invention preferably further have the following properties: A three-point bending test of a test piece (molded product) measuring 70 mm×20 mm×6.5 mm thick is 15 MPa or more after 30 days of air-dry curing. The three-point bending strength immediately after immersion in water for 7 days after 30 days of air-dry curing is 9 MPa or more. The compressive strength of a test piece (molded product) measuring 12.5 mm×12.5 mm×25.0 mm high is 30 MPa or more after 30 days of air-dry curing. The adhesiveness of a test piece (hardened product) applied to a thickness of 3 mm on a concrete plate and cured at 20° C. for 30 days is 2.0 N / mm 2 The impact resistance is 5 times or more. The three-point bending test, bending strength, compressive strength, adhesion, and impact resistance are performed by the methods described in the Examples. The cured body and molded body also have the physical properties described in the effects of the present invention.
[0052] The hardened product can be used in the same manner as hardened products of conventional cement compositions for applications such as floor coating materials, terrazzo construction methods in which colored aggregates and glass pieces are mixed in and polished after hardening, base treatment materials for coated floors, base treatment materials for waterproofing materials, repair materials for concrete structures, coating materials for interior and exterior walls, etc. In addition, the molded products can be used for applications such as interior and exterior tiles and building boards.
[0053] Among these uses, the present invention solves problems such as the reduction in strength of conventional magnesia cement-based hardened materials due to contact with moisture and water, the sweating phenomenon caused by moisture on the surface, and the tendency to expand over a long period of time, and is also preferred for use as a floor coating material because it has excellent rapid hardening properties and ease of application.
[0054] When the cured product is used as a floor coating material, the application method is not particularly limited, and the kneaded product containing the curable composition of the present invention is applied to the floor surface and cured. The method of applying the kneaded product to the floor surface is not particularly limited, and may be, for example, a metal trowel or a rake. In addition, before applying the kneaded product to the floor surface, a roughening treatment by polishing the base surface, a smoothing treatment when the base surface is uneven, and a primer coating to improve adhesion to the base may be performed. In addition, after applying the kneaded product once or multiple times depending on the condition of the base and curing it, a top coat treatment, a sealer treatment, etc. may be performed.
[0055] When the above-mentioned hardened product is used as a coating flooring material, it can provide the following effects: load-bearing capacity (it has compressive strength equal to or greater than that of ordinary Portland cement-based or high-early-strength cement-based flooring materials, so it is durable even when heavy vehicles such as forklifts and automated guided vehicles (AGVs) are driven on it), impact resistance (it can withstand the impact of heavy objects or metal tools being dropped on it), abrasion resistance (its surface hardness is high, so it is highly abrasion-resistant against frequent driving of heavy vehicles and the scraping of pallets), crack suppression (cracks occur due to hardening shrinkage in ordinary cement-based hardened products, but in the present invention, shrinkage is suppressed during the hardening reaction process, so cracks are unlikely to occur), and high whiteness (magnesia, the main raw material, has a high whiteness, and if silica, calcium carbonate, talc, or other extender pigments that do not affect the color tone are used, the hardened product will have a higher whiteness than a hardened product made mainly from ordinary Portland cement). The standard thickness is 3 mm, but by mixing aggregates with large particle sizes, it is possible to apply a thick coating of 20 mm or more at once.
[0056] Furthermore, the above-mentioned hardened product is not only applicable as a coating floor material for stores, large commercial facilities, factories, etc., but is also suitable for use as a base treatment material for damaged, missing or uneven floor surfaces, a repair material for concrete structures such as retaining walls, piers and tunnels, a finishing material for interior walls, an exterior wall finishing material, and other applications in which the product is hardened at the construction site, as well as for use as a molded product such as a molded tile for interior and exterior wall and flooring applications.
[0057] The composition of the present invention, the hardened body and the molded body of the present invention described above have the ability to absorb carbon dioxide and / or nitrogen-based malodorous substances, and therefore, focusing on the ability to absorb carbon dioxide, they can be widely used as architectural finishing materials for floors, walls, ceilings, etc., regardless of the type of building or the indoor use, and can effectively function as a measure against global warming. Also, focusing on the ability to absorb nitrogen-based malodorous substances, they can be used as interior materials for rooms, bedrooms, toilets, etc., to improve the indoor environment.
[0058] The composition of the present invention, and the cured and molded products of the present invention can absorb carbon dioxide and nitrogen-based malodorous substances. For example, if the composition of the present invention is applied to the floor surface of a building as a floor coating material with a thickness of 3 mm, the composition can absorb carbon dioxide and nitrogen-based malodorous substances in an area of 100 m. 2 It can absorb 30 kg or more, preferably 33 to 37 kg, of carbon dioxide per month. In the case of nitrogen-based malodorous substances, if the hardened material is used like a tile with a thickness of 3 mm, it can absorb 10 kg of carbon dioxide per month. 2 In terms of ammonia per unit, after 2 hours, it was 1.9 -4 mol or more, preferably 2.5×10 -4 ~2.9×10 -4 Similarly, in the case of trimethylamine, after 2 hours, 4.0 × 10 -5 mol or more, preferably 5.0×10 -5 ~5.5×10 -5 mol can be absorbed. EXAMPLES
[0059] The present invention will be described in detail below with reference to examples of the present invention, but the present invention is not limited to these examples. In each composition of the examples, the same components are used when the components have the same names.
[0060] Example 1 Physical properties of the curable composition, molded body and cured body: A kneaded product was prepared by mixing a curable composition containing the components shown in Table 1 with water. The pot life of these kneaded products was evaluated based on the following criteria: the strength of a molded product obtained by putting the kneaded product into a mold and curing it; and the cracking property of a cured product obtained by curing the kneaded product was evaluated. The results are also shown in Table 1.
[0061] Among the components listed in Table 1, magnesium oxide was first prepared by using three types of commercially available magnesium oxide (Starmag P, manufactured by Konoshima Chemical Co., Ltd., with a BET specific surface area of 1 to 5 m2). 2 / g, Star Mag U: 90-110m 2 / g, Ako Chemical Industry Co., Ltd. AM-2: 5-10m 2 The average BET specific surface area of each of the magnesium oxide particles (1.0 μm / g) was measured by the following method. Then, the magnesium oxide particles were appropriately mixed to prepare magnesium oxide particles having each average BET specific surface area.
[0062] [Table 1]
[0063] <Average BET specific surface area measurement method> The average BET specific surface area was measured using an automatic flow type specific surface area measuring device (Flowsorb 2300 type: manufactured by Shimadzu Corporation) in accordance with JIS R 1626 (Method for measuring specific surface area of fine ceramic powder by gas adsorption BET method).
[0064] <Method for determining pot life> The time until the viscosity exceeded 20,000 mPa s was measured, starting immediately after adding water to the curable composition and stirring and mixing for 2 minutes in a room at 20°C. The viscosity was measured in accordance with JIS Z 8803 (Method for measuring viscosity of liquids) using a BH-type rotational viscometer, model BHII (manufactured by Toki Sangyo Co., Ltd.), at a rotation speed of 20 rpm.
[0065] <Method for determining strength of cured product> In a room at 20°C, a specified amount of water was added to the curable composition, and the mixture was stirred and mixed for 2 minutes. The mixture was poured into a silicone rubber mold so that the thickness of the mixture was about 7 mm, and left to stand on a flat surface. After 5 days of curing, the cured molded body was removed from the mold, and a molded body was obtained with dimensions of 70 mm x 20 mm x 6.5 mm thick. The molded body was further left to stand in air for 25 days, and after a total of 30 days of air-dry curing, it was immersed in water, and after 7 days had passed, it was taken out of the water and immediately thereafter a three-point bending test was performed to determine the three-point bending strength.
[0066] (Test conditions) Testing machine: Shimadzu Corporation Autograph Model AG-50kNXplus Test speed: 1mm / min Distance between fulcrums L: 50mm Indenter radius: 5mm Support radius: 5mm
[0067] (calculation formula) σ = (3FL) / (2bh 2 ) σ: Bending strength (MPa) F: Load at break (N) L: Distance between fulcrums (mm) b: Test piece width (mm) h: test piece thickness (mm)
[0068] <Crackability assessment> A flexible board measuring 450mm x 450mm was coated with a primer of Saiden Chemical Co., Ltd.'s water-based resin AD-8521 (acrylic-styrene emulsion) and dried to prepare a base plate. In a room at 20°C, a specified amount of water was added to the curable composition, and the mixture was stirred and mixed for 2 minutes. The mixture was then evenly coated on the base plate to a thickness of 3mm over the entire surface to obtain a cured body. This was left to stand for 30 days, after which it was visually observed to determine whether the cured body had any cracks.
[0069] In composition 9, the gypsum hemihydrate was 5.0% relative to the mass of magnesium oxide, and cracking was confirmed, but in compositions 1 to 8 and composition 10, the gypsum hemihydrate was 12.5 to 30.0% relative to the mass of magnesium oxide, and no cracking was confirmed. In particular, compositions 2, 3, 6, and 7 have an average BET specific surface area of magnesium oxide of 5 to 25 m 2 / g range, and further the mass ratio of magnesium oxide to magnesium carbonate was in the range of 3 to 10:1, so that the pot life and the strength of the cured product were well balanced.
[0070] Example 2 Physical properties of the curable composition and molded article: A kneaded product was prepared by mixing water with a curable composition containing the components shown in Table 2. The pot life of the kneaded product, the strength of the molded product, and the cracking property of the cured product were evaluated in the same manner as in Example 1. The results are also shown in Table 2.
[0071] [Table 2]
[0072] Composition 11 did not contain any silicate compounds and had low hardened strength, whereas compositions 12 to 17 contained one or more silicate compounds at 0.75 to 25.0% relative to the mass of magnesium oxide, and showed hardened strengths of 9 MPa or more.
[0073] Example 3 Physical properties of molded body: A kneaded mixture was prepared by mixing a curable composition containing the components shown in Table 3 with water, and then a molded body was produced in the same manner as in Example 1. This was subjected to a three-point bending strength test in an air-dry curing environment at a temperature of 20°C after 10, 20, 30, 50, and 100 days, in the same manner as in Example 1, to measure the bending strength. The results are shown in Table 4.
[0074] [Table 3]
[0075] The kneaded material was then poured into a silicone mold and cured to produce a molded product measuring 12.5 mm x 12.5 mm x 25.0 mm in height. Compression tests were performed after 10, 20, 30, 50, and 100 days of air-dry curing, using the following method, to measure the compressive strength. The results are shown in Table 4.
[0076] <Compression test> (Compression test conditions) Testing machine: Shimadzu Corporation Autograph Model AG-50kNXplus Test speed: 1mm / min
[0077] (calculation formula) σ=F / A σ: Compressive strength (MPa) F: Yield point load (N) A: Cross-sectional area of the test piece before stress is applied
[0078] [Table 4]
[0079] It was confirmed that the bending strength and compressive strength of the molded body gradually improved with the passage of curing days.
[0080] Example 4 Physical properties of the cured product of the curable composition: A concrete plate measuring 300 mm long x 300 mm wide x 50 mm thick was placed horizontally, and after removing the weak surface layer using sandpaper, a water-based resin AD-8521 (acrylic-styrene emulsion) manufactured by Saiden Chemical Industries, Ltd. was applied as a primer and allowed to dry. After drying, the same mixture as in Example 3 was applied to a thickness of 3 mm on top to form a hardened body. This was then cured at 20°C for 30 days, and the test described in Table 5 was carried out using this as a test specimen (concrete base, hardened body on top). The results are also shown in Table 5.
[0081] [Table 5]
[0082] The adhesiveness of the cured body was good. The impact resistance of the cured body also showed good results.
[0083] Example 5 Effect of hardenable compositions on ferrous materials: A kneaded material similar to that in Example 3 was prepared and poured into a plastic container measuring 100 mm in length and 50 mm in width to a depth of about 5 mm, and an iron plate measuring 20 mm in length, 50 mm in width, and 2 mm in thickness was placed vertically in the container. After leaving the container for 7 days, the material was visually observed and no changes such as discoloration were observed.
[0084] Example 6 Carbon Dioxide Absorption Test: A kneaded product was prepared by mixing 100 parts by mass of the curable composition of composition 17 of Example 2 and 50 parts by mass of water. 85.5 g of the kneaded product was poured into a test mold (129.5 mm x 129.5 mm) so that the thickness of the cured product was 3 mm. Immediately after, this was placed in a Smart Bag PA (manufactured by GL Sciences, Inc.: actual volume 2.7 L), which is a gas collection bag made of a vinyl alcohol-based polymer film, and heat-sealed to seal it. Gas with an adjusted carbon dioxide concentration was injected from a valve, and immediately after that, the carbon dioxide concentration in the bag was measured using a gas detector tube method (Kitagawa gas detector tube: models 126SH and 126UH). The carbon dioxide concentration immediately after the start was 37.3%. For one week after the start of the measurement, the carbon dioxide concentration was measured approximately every day, and the amount of carbon dioxide absorbed was then replenished. After 100 hours had passed, the carbon dioxide concentration was measured and replenished approximately every 7 days. The results are shown in FIG. 1.
[0085] As is clear from Figure 1, it was found that the curable composition of the present invention absorbs carbon dioxide continuously during curing and after the initial curing (after 100 hours). The amount of carbon dioxide absorbed from immediately after being placed in the bag until 858 hours later was 3110 ml, which indicates that the curable composition of the present invention absorbs 5.75 g of carbon dioxide per 85.5 g. A 510 kg sample of the curable composition of the present invention was placed in a bag with a thickness of 3 mm and an area of 100 m 2 When installed in this manner, it will absorb 34.3 kg of carbon dioxide within 858 hours, which is significantly higher than the 14 kg absorbed by a 50-year-old cedar tree in one year (Kanto Forest Management Bureau website (https: / / www.rinya.maff.go.jp / kanto / hukusima / office / forest / knowledge / breathing.html)).
[0086] Example 7 Carbon Dioxide Absorption Test: A kneaded product was prepared by mixing 100 parts by mass of the curable composition of composition 17 of Example 2 and 50 parts by mass of water. 85.5 g of this kneaded product was cured for 24 hours to form a tile with a thickness of 3 mm and a size of 129.5 mm x 129.5 mm. 24 hours after the material was poured, the entire surface of the cured product was coated twice with a thin coating material for preventing water-based acrylic resin stains (Verasia M Topcoat: manufactured by ABC Shokai Co., Ltd.), and the product was left to dry for 1 hour, and then placed in a Smart Bag PA (manufactured by GL Science Co., Ltd., actual volume 2.5 L), which is a gas collection bag made of a vinyl alcohol polymer film, and then the open part was heat-sealed to seal it, and gas with an adjusted carbon dioxide concentration was injected from the valve, and immediately after that, the carbon dioxide concentration was measured using a gas detector tube method (Kitagawa gas detector tube: models 126SH and 126UH). The carbon dioxide concentration immediately after the start was 13.1%. For the first week after the start of the measurements, the carbon dioxide concentration was measured approximately every day, after which the amount of carbon dioxide absorbed was replenished. After 100 hours had passed, the carbon dioxide concentration was measured and replenished approximately every seven days. The results are shown in Figure 2.
[0087] As is clear from Figure 2, it was found that the curable composition of the present invention absorbs carbon dioxide continuously without being affected by the top coat. The amount of carbon dioxide absorbed from immediately after being placed in the bag until 1004 hours was 2677.5 ml, which shows that the curable composition of the present invention absorbs 4.95 g of carbon dioxide per 85.5 g. When 510 kg of the curable composition of the present invention was placed in a bag with a thickness of 3 mm and an area of 100 m, 2 When installed in this way, it will absorb 29.5 kg of carbon dioxide within 1,004 hours (excluding the amount of carbon dioxide absorbed within 24 hours of mixing the materials), which is significantly higher than the 14 kg absorbed by a 50-year-old cedar tree in one year.
[0088] Example 8 Ammonia absorption test: A kneaded product was prepared by mixing 100 parts by mass of the curable composition of composition 17 of Example 2 and 50 parts by mass of water. 85.5 g of the kneaded product was poured into a test mold (129.5 mm x 129.5 mm) so that the thickness of the cured product was 3 mm, and immediately after that, it was placed in a Tedlar bag (GL Sciences, actual volume 2.7 L), which is a polypropylene gas collection bag, and sealed by heat sealing. Gas with ammonia concentration adjusted in advance was immediately injected from the valve, and the ammonia concentration in the bag was measured over time using a gas detector tube method (Kitagawa gas detector tube: Model 105SD, 105SE) immediately after that. The ammonia concentration immediately after the start was 17.0%. The results are shown in Table 6. [Table 6]
[0089] As is clear from these results, it was found that the curable composition of the present invention absorbs ammonia during curing.
[0090] Example 9 Ammonia absorption test: A kneaded mixture was prepared by mixing 100 parts by mass of the curable composition of composition 17 of Example 2 with 50 parts by mass of water. This kneaded mixture had a size of 100 mm × 100 mm × thickness of 3 mm (sample area 100 cm 2 ) hardened body and left to cure for 28 days in a normal room environment. This was placed in a polyvinyl fluoride gas repair Tedlar bag (GL Sciences Inc.), which was then heat sealed to seal, and gas with an adjusted ammonia concentration was injected through the valve. Immediately after this, the ammonia concentration was measured at regular intervals using a gas detector tube (Kitagawa gas detector tube: No. 105SD or No. 105SE). The ammonia concentration immediately after the start was 29 ppm. The results are shown in Table 7.
[0091] [Table 7]
[0092] As is clear from these results, it was found that the curable composition of the present invention absorbs ammonia even after curing.
[0093] Example 10 Ammonia absorption test: 100 parts by mass of the curable composition of composition 17 of Example 2 and 50 parts by mass of water were mixed to prepare a kneaded product, and the resulting product was measured in a size of 100 mm × 100 mm × thickness of 3 mm (sample area: 100 cm 2 ) was used to prepare a hardened product. 24 hours after mixing the materials, the entire surface of this hardened product was coated twice with a thin film coating material for preventing water-based acrylic resin stains (Verasia M Topcoat, manufactured by ABC Shokai Co., Ltd.), and then left to cure for 28 days in a normal indoor environment. This was placed in a polyvinyl fluoride gas collection bag, which was then heat sealed to seal it, and the ammonia concentration was measured immediately afterwards using a gas detector tube (Kitagawa gas detector tube: models 105SD and 105SE). The ammonia concentration immediately after starting was 44 ppm. The results are shown in Table 8.
[0094] [Table 8]
[0095] As is clear from these results, it was found that the cured product of the present invention continuously absorbs ammonia without being affected by the top coat.
[0096] Example 11 Trimethylamine Absorption Test: A kneaded product was prepared by mixing 100 parts by mass of the curable composition of composition 17 of Example 2 and 50 parts by mass of water. 85.5 g of the kneaded product was poured into a test mold (129.5 mm x 129.5 mm) so that the thickness of the cured product was 3 mm, and immediately after that, it was placed in a Tedlar bag (manufactured by GL Sciences, Inc., actual volume 2.7 L), which is a gas collection bag made of polyvinyl fluoride, and sealed by heat sealing. Immediately after that, gas in which the concentration of trimethylamine had been adjusted in advance was injected from a valve, and the trimethylamine concentration in the bag was measured over time using a gas detector tube method (Kitagawa gas detector tube: model 105SE). The trimethylamine concentration immediately after the start was 11.5%. The results are shown in Table 9.
[0097] [Table 9]
[0098] As is clear from these results, it was found that the curable composition of the present invention absorbs trimethylamine during curing.
[0099] Example 12 Trimethylamine Absorption Test: A kneaded mixture was prepared by mixing 100 parts by mass of the curable composition of composition 17 of Example 2 and 50 parts by mass of water. This kneaded mixture was made into a hardened body of 129.5 mm x 129.5 mm x 3 mm thick, and left to cure indoors for 14 days. This was placed in a Tedlar bag (GL Sciences, Inc., actual volume 2.7 L), a polyvinyl fluoride gas collection bag, and sealed by heat sealing. Immediately after that, gas with a previously adjusted trimethylamine concentration was injected through a valve. Immediately after that, the trimethylamine concentration was measured using a gas detector tube method (Kitagawa gas detector tube: Model 105SE). The trimethylamine concentration immediately after the start was 15 ppm. The results are shown in Table 10.
[0100] [Table 10]
[0101] As is clear from these results, it was found that the curable composition of the present invention absorbs trimethylamine even after curing.
[0102] As described above, it has become clear that the curable composition of the present invention absorbs carbon dioxide and nitrogen-based malodorous substances such as ammonia and trimethylamine during curing and even when the cured product or molded product is used as a finishing building material. This is presumably due to the absorption action accompanying the curing reaction of the curable composition of the present invention, or the adsorption action of pores in the hardened product structure. For this reason, a curable composition containing magnesium oxide, magnesium carbonate, hemihydrate gypsum, and a silicate compound, which contains 30 to 60 mass % of magnesium oxide and has an average BET specific surface area of 5 to 25 m2, is used. 2 / g, the mass ratio of magnesium oxide to magnesium carbonate is 3 to 10:1, the amount of hemihydrate gypsum is 6 to 25 mass% relative to the mass of magnesium oxide, and any of the compositions not containing magnesium chloride will absorb carbon dioxide and / or nitrogen-based malodorous substances.
[0103] Example 13 Physical properties of compacts after carbon dioxide curing: A kneaded mixture was prepared by mixing 100 parts by mass of the curable composition of composition 17 of Example 2 with 50 parts by mass of water, and then a molded body was prepared in the same manner as in Example 1. This was aged in the air for 2 days at a temperature of 20°C, and then the test body was placed in a Smart Bag PA (GL Sciences Inc.), heat-sealed, and then aged by injecting carbon dioxide to maintain the carbon dioxide concentration at 10-20%. A three-point bending strength test was performed in the same manner as in Example 1 after 13 and 30 days of aging, and the bending strength was measured. The samples aged in the air were used for comparison. The results are shown in Table 11.
[0104] [Table 11]
[0105] It has become clear that the strength of the molded article of the present invention is improved by absorbing carbon dioxide. [Industrial Applicability]
[0106] The hardenable composition of the present invention can be used for absorbing carbon dioxide and / or nitrogen-based malodorous substances in addition to various applications similar to those of conventional cement compositions. That's all
Claims
1. A hardenable composition containing magnesium oxide, magnesium carbonate, hemihydrate gypsum, and a silicate compound, Contains 30 to 60 mass % magnesium oxide, Magnesium oxide with an average BET specific surface area of 5 to 25 m 2 / g, The mass ratio of magnesium oxide to magnesium carbonate is 3 to 10:1, The amount of hemihydrate gypsum is 6 to 25% by mass based on the mass of magnesium oxide, Does not contain magnesium chloride A curable composition for absorbing carbon dioxide and / or nitrogen-based malodorous substances, comprising:
2. 2. The curable composition for absorbing carbon dioxide and / or nitrogen-based malodorous substances according to claim 1, wherein the magnesium carbonate is basic magnesium carbonate.
3. 2. The curable composition for absorbing carbon dioxide and / or nitrogen-based malodorous substances according to claim 1, wherein the silicate compound is one or more selected from the group consisting of wollastonite, metakaolin, zircon and dry silica.
4. 2. The curable composition for absorbing carbon dioxide and / or nitrogen-based malodorous substances according to claim 1, wherein the silicate compound is present in an amount of 0.1 to 30% by mass based on the mass of magnesium oxide.
5. The curable composition for absorbing carbon dioxide and / or nitrogen-based malodorous substances according to claim 1, further comprising one or more compounding agents selected from the group consisting of fillers, pigments, water-reducing agents, defoamers, wetting and dispersing agents, viscosity adjusters, anti-sagging agents, aqueous resins, and aggregates.
6. A hardened body for absorbing carbon dioxide and / or nitrogen-based malodorous substances, obtained by hardening a mixture of the hardening composition for absorbing carbon dioxide and / or nitrogen-based malodorous substances according to any one of claims 1 to 5 and water.
7. A molded body for absorbing carbon dioxide and / or nitrogen-based malodorous substances, which is obtained by pouring a mixture of the hardening composition for absorbing carbon dioxide and / or nitrogen-based malodorous substances according to any one of claims 1 to 5 and water into a formwork and then hardening the mixture.
8. A method for absorbing carbon dioxide and / or nitrogen-based malodorous substances, comprising: kneading the carbon dioxide and / or nitrogen-based malodorous substances absorbing hardening composition according to any one of claims 1 to 5 with water; applying the mixture to a floor surface; and hardening the mixture.
9. A method for absorbing carbon dioxide and / or nitrogen-based malodorous substances, comprising: kneading the carbon dioxide and / or nitrogen-based malodorous substances absorbing hardening composition according to any one of claims 1 to 5 with water; applying the mixture to a wall surface; and hardening the mixture.
10. A method for absorbing carbon dioxide and / or nitrogen-based malodorous substances, comprising: pouring a mixture of the hardening composition for absorbing carbon dioxide and / or nitrogen-based malodorous substances according to any one of claims 1 to 5 and water into a formwork, and then hardening the mixture.
11. A method for absorbing carbon dioxide and / or nitrogen-based malodorous substances, comprising attaching the carbon dioxide and / or nitrogen-based malodorous substance absorbing molded article according to claim 7 to a floor surface.
12. A method for absorbing carbon dioxide and / or nitrogen-based malodorous substances, comprising attaching the carbon dioxide and / or nitrogen-based malodorous substance absorbing molded article according to claim 7 to a wall surface.
Citation Information
Patent Citations
Offensive smell generation suppressing solidifying material and solidification method
JP2003190992A
Environmental improvement cement composition
JP2003226562A
Material for earth and sand structure, surface protecting construction method for inclined face, lining face, and tunnel lining face using the same, and slope protecting construction method
JP2005120349A
Method for constructing soil structure, and soil structure
JP2012087017A
Composite adsorbing and absorbing chemical substance and production method thereof
JP2015205267A
